Vibration–rotation interactions in H2, HD and D2 : centrifugal distortion factors and the derivatives of polarisability invariants. (3rd March 2020) - Raj, Ankit; Witek, Henryk A.; Hamaguchi, Hiro-o
ABSTRACT: We report the correction factors for centrifugal distortion in Raman intensities for pure rotation (O0- and S0-branch) and vibration–rotation (O1- and S1-branch) transitions in the ground electronic state of H2, HD and D 2 . These factors are presented for 52 selected excitation wavelengths and for the initial rotational states, J = 2 − 21 . This data is useful in applications of intensity calibration of spectrometers and the spectroscopy of flames. The classical treatment of centrifugal distortion involved the expansion of polarisability anisotropy ( γ ) over the internuclear distance, while assuming the diatomic molecule behaves as a harmonic oscillator. Here, this approximation of polarisability invariants as a Taylor series expansion is tested, revealing that truncation up to the second-order derivatives of mean polarisability ( α ¯ ) and polarisability anisotropy ( γ ) gives faithful representations, yielding accurate expectation values with error < 0.2 %, for the ground rovibrational state and for the fundamental transition. GRAPHICAL ABSTRACT: UF0001